Enhancing Scientific Writing Competence through Participatory Academic Writing Training: A Community Engagement Program for University Students - Niswatin Nurul Hidayati (Lembaga Penelitian dan Publikasi Ilmiah, Yayasan Yuta Pendidikan Cerdas, 2026)
Scientific writing competence is an essential academic skill that enables university students to communicate research findings effectively and contribute to scholarly knowledge. However, many students continue to experience difficulties in developing scientific manuscripts due to limited experience in academic writing, literature review development, citation management, and research organization. To address these challenges, a community engagement program was conducted to enhance the scientific writing competence of students in the Retail Management Study Program at Institut Teknologi dan Bisnis (ITB) Tuban through participatory academic writing training. The program employed a participatory approach consisting of three stages: a needs assessment, participatory academic writing training, and guided writing practice with mentoring. Data were collected through observations, questionnaires, documentation, and participants' writing assignments and were analyzed using descriptive qualitative and quantitative approaches. The findings indicate that the training successfully improved students' understanding of scientific writing principles, research topic formulation, manuscript organization, literature review development, APA citation practices, and the use of reference management software. The mentoring and hands-on writing activities also increased participants' confidence, engagement, and ability to produce structured scientific manuscripts. Furthermore, the participatory learning approach fostered collaborative learning and encouraged students to actively exchange ideas and receive constructive feedback throughout the writing process. This community engagement program demonstrates that integrating interactive instruction, guided practice, and continuous mentoring provides an effective strategy for strengthening scientific writing competence and promoting academic literacy among university students. The program is expected to contribute to the development of a sustainable academic writing culture and support students' readiness for research and scientific publication.